Development of Some Novel Suction-Based Correlations for Swell Behavior of Expansive Soils - Bakht Zamin; Hassan Nasir; Khalid Mehmood; Qaiser Iqbal; M. Tariq Bashir; Asim Farooq (Advances in Civil Engineering)
Swelling and shrinkage are the two distinctive characteristics of expansive soils, and due to this behavior, these soils are considered a natural hazard for infrastructure. Many structures in different regions have been impaired due to the swell/shrink behavior of the expansive soil. Most of the severe distress is impeded because of the inherent suction (negative pore water pressure) present in expansive soils. Both suction and swelling parameters are greatly affected by the surrounding moisture content. Due to this feature of expansive soil, geotechnical engineers are interested in utilizing the suction-based correlations for the assessment of unsaturated expansive soils. The current investigation was carried out to develop novel correlations incorporating lab testing and field instrumentation. To fulfill the objectives, eight sites of the local expansive soil in Pakistan were selected for samples collection and field testing. Conventional odometer testing was conducted to measure the swell pressure (Sp) and swell potential (S) of the fabricated/remolded specimens. Gypsum block (G-block) sensors were additionally utilized for estimating the matric suction in the field. To expand the database, the previously published data of the same nature was also incorporated. Based on the results, the power form of the novel correlations (suction-based) is highly significant for estimating (Sp), while for swell potential, the logarithmic correlation with R2 = 0.6551 is more significant than other forms of correlations. The proposed suction-based correlation can be equally utilized for the estimation of field suction as well as for swell behavior of expansive soil having a plasticity index (PI) ≥ 22%.